The Effectiveness of Blended Learning in Increasing Prospective Physics Teacher Students’ Learning Motivation and Problem-Solving Ability - Ketut Suma; I.N.P Suwindra; Rai Sujanem (Jurnal Pendidikan Indonesia, 2020)
Advances in information technology have led to innovative learning methods that combine traditional and online learning, known as blended learning. This pre-experimental study aims to analyze the effectiveness of blended learning in increasing prospective physics teacher students’ learning motivation and problem-solving ability. There were 14 students who participated in this study. They were involved in 70% of face-to-face learning and 30% in online learning. The data of learning motivation were collected by the questioner and the data of problem-solving ability were collected by test. The research hypotheses were tested by non-parametric statistics, namely the sign test. The results of the study indicate that the pre-test score mean of learning motivation was 67.21 (SD= 5.45), which was in the medium level and the post-test score mean was 74.98 (SD=5.93), which was at a high level. The pre-test score means of problem-solving was 33. 43 (SD = 4.90) which was at a low-level and the post-test score mean was 63.54 (SD =2.35), which was at a moderate level. The one side sign test shows the calculated ZC= 3.43, which was higher than standard Z at a 5% significance level. The mean score of prospective physics teacher students’ learning motivation and problem-solving ability between before and after learning was significantly different. From this finding can be concluded that blended learning effective in increasing  prospective physics teacher students’ learning motivation and problem-solving ability.